The effect of adding L-carnitine to omega-3 fatty acid diets on productive performance, oxidative stability, cholesterol content, and yolk fatty acid profiles in laying hens - Hasan Rouhanipour; Seyed Davood Sharifi; Gholam-Hossein Irajian; Morteza Pashaei Jalal (Poultry Science, 2022)
ABSTRACT: In this study, different levels of Omega-3 fatty acids and L-carnitine (LC) were used in diets for laying hens. The effects of these supplements were examined on productive performance, antioxidant properties, cholesterol content, and yolk fatty acid profiles in the laying hens. A population of 120 Lohmann LSL-Lite laying hens (34-wk-old) were used in 2 × 3 factorial arrangements with 2 diets (control = 0.031 and 0.48% omega-3 fatty acids) and 3 levels of L-carnitine (0, 100, 200 mg/kg of diet) in a completely randomized design with 6 treatments. While having 5 replicates and 4 birds per replicate, the total period of the experiment lasted for 10 wk. The eggs were weighed daily, parallel to measurements of egg production, daily feed intake, feed conversion ratio, and egg mass. When the hens reached 44 wk of age, the measurements were aimed at fatty acid profiles, malondialdehyde (MDA), and cholesterol concentration in egg yolk. Feeding the hens on diets enriched by omega-3 fatty acids led to higher levels of egg production than those fed on control diets, but their daily feed intake was generally lower (P < 0.05). Egg weight decreased in birds that were fed on diets enriched with omega-3 fatty acids without L-carnitine, or with diets which contained 100 mg/kg L-carnitine, compared to control diets which contained 0 mg/kg L-carnitine (P < 0.05). Egg mass increased in birds that were fed on diets enriched with omega-3 fatty acids and which contained 200 mg/kg L-carnitine, compared to the control diet with 0 or 100 mg/kg L-carnitine (P < 0.05). The analysis of fatty acid profiles showed that L-carnitine and omega-3 fatty acids caused a significant increase in the percentage of eicosapentaenoic acid (EPA), docosahexaenoic  acid (DHA), C18: 1 (n-9), arachidonic acid (ARA) C20: 4 (n-6), and Σ n-3 in the eggs of birds (P < 0.05). Based on the results, adding L-carnitine (200 mg/kg) to diets that were already enriched with omega-3 fatty acids increased the level of production and led to a longer maintenance of fatty acids in the eggs. Also, oxidative stability was enhanced in the yolk of eggs.